Development and characterization of photoprotective formulations containing keratin particles (Brazilian Journal of Pharmaceutical Sciences, 2019)
This work deals with development and evaluation of MFQ protective formulation, which contains two organic filters, namely: octyl-p-methoxycinnamate (OMC) and benzophenone-3 (BP-3); a photostabilizing agent called ethylhexylmethoxycrylene (EHMCR) and keratin particles. The MFQ formulation was evaluated in order to measure its pH, spin-spin lattice relaxation time (T2H), occlusivity factor, formulation efficacy, photostability and skin permeation, as well as keratin particle properties. Keratin particle size increased when incorporated to formulation, however, it did not affect pH. The MFQ formulation was found to be photostable and photoprotective, as evidenced by sunlight photostability test, sun protection factor (SPF), UVA/UVB ratio and critical wavelength. Interaction between keratin particles and active substances (OMC, BP-3 and EHMCR) was evidenced by T2H measurements. Evidences suggest that keratin reduces the permeation of both UV filters employed along this study, therefore, it can be stated that keratin has a promising potential for use in sunscreen formulations.